2004
DOI: 10.12693/aphyspola.106.367
|View full text |Cite
|
Sign up to set email alerts
|

Emission from Mesoscopic-Size Islands Formed in a GaAs/AlAs Double Layer Structure

Abstract: The nature of sharp emission lines which are present in macro--luminescence experiments on a type-II GaAs/AlAs double quantum well structure is discussed. The experiments, which also include micro-luminescence measurements, allowed us to conclude that the sharp emission lines observed originate from lateral GaAlAs islands of a few µm in diameter. They serve as efficient type-I recombination centers for indirect excitons and/or carriers which diffuse in the GaAs/AlAs QW structure and strongly affect the emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…This is expected since the eh exchange interaction inuences neither the initial (where the two majority carriers are forming closed shell with J e = 0) nor the nal state (only one carrier left). It has been previously reported that the X + emission is not observed and the X − is clearly observed in non-resonant excitation regime [9], due to the very long lifetime of the indirect excitons at the type-II GaAs/AlAs bilayer [14]. In a quasi-resonant excitation regime, the emission related to the negatively charged exciton (X − ) has also been observed and identied, based on the particular shape of the QD conning potential, signicantly deeper for electrons than for holes [11].…”
Section: Resultsmentioning
confidence: 96%
“…This is expected since the eh exchange interaction inuences neither the initial (where the two majority carriers are forming closed shell with J e = 0) nor the nal state (only one carrier left). It has been previously reported that the X + emission is not observed and the X − is clearly observed in non-resonant excitation regime [9], due to the very long lifetime of the indirect excitons at the type-II GaAs/AlAs bilayer [14]. In a quasi-resonant excitation regime, the emission related to the negatively charged exciton (X − ) has also been observed and identied, based on the particular shape of the QD conning potential, signicantly deeper for electrons than for holes [11].…”
Section: Resultsmentioning
confidence: 96%
“…The sample under study consists of a type II GaAs/ AlAs double quantum well structure [4,5] (see inset in Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…These dots show remarkably low surface density, at the level of 10 5 − 10 6 cm −2 . Their emission spectra are dispersed in a wide energy range, 1.56-1.68 eV, [14][15][16][17][18][19][20] due to the spread in the lateral extent of the confining potential.…”
Section: Sample and Experimental Setupsmentioning
confidence: 99%